2008
DOI: 10.1097/wnr.0b013e3282f7c4d3
|View full text |Cite
|
Sign up to set email alerts
|

Facing a real person: an event-related potential study

Abstract: Although faces are typically perceived in the context of human interaction, face processing is commonly studied by displaying faces on a computer screen. This study on event-related potential examined whether the processing of faces differs depending on whether participants are viewing faces live or on a computer screen. In both the conditions, the participants were shown a real face, a dummy face, and a control object. N170 and early posterior negativity discriminated between faces and control object in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Attention direction adaptation (Teufel et al, 2009) and automatic attention shifts by head orientation cues (Teufel et al, 2010a) has shown to be modulated depending on whether the participants were lead to believe that the other person was capable of seeing them or not via a video-link. Compatible with our previous propositions : Pönkänen et al, 2008, Teufel et al (2010b) proposed that mental-state attributions could modulate even the basic perceptual processing of social stimuli. Thus, the lack of the measured affective and motivational physiological responses to face pictures in the present as well as in our previous study (Hietanen et al, 21 2008) may reflect the effects of mental-state attributions already at the early stage perceptual processing.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Attention direction adaptation (Teufel et al, 2009) and automatic attention shifts by head orientation cues (Teufel et al, 2010a) has shown to be modulated depending on whether the participants were lead to believe that the other person was capable of seeing them or not via a video-link. Compatible with our previous propositions : Pönkänen et al, 2008, Teufel et al (2010b) proposed that mental-state attributions could modulate even the basic perceptual processing of social stimuli. Thus, the lack of the measured affective and motivational physiological responses to face pictures in the present as well as in our previous study (Hietanen et al, 21 2008) may reflect the effects of mental-state attributions already at the early stage perceptual processing.…”
Section: Discussionsupporting
confidence: 69%
“…Notably, in many of these studies (i.e., Conty et al, 2007;Mason et al, 2005;Sato et al, 2008;Schilbach et al, 2006) discrimination of gaze direction or some other explicit task related to face categorization was employed. In our aforementioned studies, instead, the faces were observed without a concomitant task Pönkänen et al, in press;Pönkänen et al, 2008). Thus, the question arises, whether the lack of a task, related to the gaze direction or not, might have contributed to the lack of gaze direction effects in the picture presentation mode in these studies.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Importantly, the mere presence or even assumed presence of other people changes the way the human brain processes sensory input. For example, early electrophysiological responses to faces are larger when the observers see the face of a real person, rather than the face of a dummy [35]. Similarly, interaction with 'live' rather than recorded persons elicits stronger brain responses [36].…”
Section: Contextual Effects In Social Situationsmentioning
confidence: 99%
“…Auditory ERPs are utilized in anesthesia control [1,3,4] and in assessment of word deafness after subcortical hemorrhage [5]. In this work, we employ ERPs, more specifically VEPs, measured in response to seeing human faces with different emotional expressions [6,7,8], a type of visual stimuli used in psychological research.…”
Section: Introductionmentioning
confidence: 99%